2016
DOI: 10.3389/fnhum.2016.00411
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Slow Fluctuations in V1 Impact on Visual Perception

Abstract: The human brain’s ongoing activity is characterized by intrinsic networks of coherent fluctuations, measured for example with correlated functional magnetic resonance imaging signals. So far, however, the brain processes underlying this ongoing blood oxygenation level dependent (BOLD) signal orchestration and their direct relevance for human behavior are not sufficiently understood. In this study, we address the question of whether and how ongoing BOLD activity within intrinsic occipital networks impacts on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Early work with human subjects (using stimulus detection tasks and event-driven fMRI paradigms) linked performance on tasks to resting BOLD amplitude in various brain regions (Boly et al, 2007; Eichele et al, 2008; Sadaghiani et al, 2009). Using dynamic rsfMRI, fluctuations in correlation between brain regions or networks have shown similar effects within a variety of tasks (Cassidy et al, 2016; Gonzalez-Castillo et al, 2015; Jia et al, 2014; Madhyastha et al, 2015; Mooneyham et al, 2017; Sadaghiani et al, 2015; Telesford et al, 2016; Thompson et al, 2013a; Weissman et al, 2006), as have amplitudes within resting state networks themselves (Wohlschlager et al, 2016). Presentation of stimuli (Nummenmaa et al, 2014; Raz et al, 2012), as well as spontaneous state changes including eye closures (Wang et al, 2016), daydreaming (Kucyi and Davis, 2014), sleep state (Tagliazucchi and Laufs, 2014; Wilson et al, 2015) and deprivation (Kaufmann et al, 2016) all alter dynamic rsfMRI measurements.…”
Section: 2 Dynamic Rsfmri Changes With the Shifting States Of The Bmentioning
confidence: 99%
“…Early work with human subjects (using stimulus detection tasks and event-driven fMRI paradigms) linked performance on tasks to resting BOLD amplitude in various brain regions (Boly et al, 2007; Eichele et al, 2008; Sadaghiani et al, 2009). Using dynamic rsfMRI, fluctuations in correlation between brain regions or networks have shown similar effects within a variety of tasks (Cassidy et al, 2016; Gonzalez-Castillo et al, 2015; Jia et al, 2014; Madhyastha et al, 2015; Mooneyham et al, 2017; Sadaghiani et al, 2015; Telesford et al, 2016; Thompson et al, 2013a; Weissman et al, 2006), as have amplitudes within resting state networks themselves (Wohlschlager et al, 2016). Presentation of stimuli (Nummenmaa et al, 2014; Raz et al, 2012), as well as spontaneous state changes including eye closures (Wang et al, 2016), daydreaming (Kucyi and Davis, 2014), sleep state (Tagliazucchi and Laufs, 2014; Wilson et al, 2015) and deprivation (Kaufmann et al, 2016) all alter dynamic rsfMRI measurements.…”
Section: 2 Dynamic Rsfmri Changes With the Shifting States Of The Bmentioning
confidence: 99%
“…Within the frequency range we have studied (<0.1 Hz), stimulus detection is predicted by spontaneous slow negative cortical shifts in EEG signals (Devrim, Demiralp, Kurt, & Yücesir, 1999) and by the phase of ongoing EEG oscillations in the infraslow range (Monto et al, 2008). Additionally, previous studies have demonstrated relationships between performance on visual detection tasks and prestimulus fMRI activity recorded a few seconds before stimulus onset (Coste & Kleinschmidt, 2016; Wohlschläger et al, 2016; Schölvinck, Friston, & Rees, 2012; Hesselmann et al, 2008), and fMRI connectivity between brain regions at very slow frequencies is significantly correlated with performance across participants in an executive control task (Xu et al, 2014) and a visual attention task (Griffis, Elkhetali, Burge, Chen, & Visscher, 2015). Our results extend these findings by showing that spatial attention suppresses slow endogenous fluctuations in occipital and parietal cortex and that reduced endogenous activity predicts performance on a visual detection task.…”
Section: Discussionmentioning
confidence: 96%
“…Perceptual performance is affected by intrinsic neural activity immediately before stimulus presentation (Busch, Dubois, & VanRullen, 2009; Mathewson, Gratton, Fabiani, Beck, & Ro, 2009; Supèr, van der Togt, Spekreijse, & Lamme, 2003), including very slow (<0.1 Hz) fluctuations in activity (Monto, Palva, Voipio, & Palva, 2008). In addition, ongoing fMRI signals before initiation of visual perceptual tasks predict behavior (Coste & Kleinschmidt, 2016; Wohlschläger et al, 2016; Hesselmann, Kell, & Kleinschmidt, 2008; Weissman, Roberts, Visscher, & Woldorff, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A backward-masked visual perception task ( Figure 1A ) was adapted from (Wohlschläger et al, 2016 ; Glim et al, 2020 ; see also, Haynes et al, 2005 ) to measure visual confidence. fMRI data were concurrently recorded during the task.…”
Section: Methodsmentioning
confidence: 99%